LINE as Super App: Platformization in East Asia. (June 2020) - Steinberg, Marc
This article examines the transformative effects of platforms on cultural production through an analysis of the LINE "super app." Super apps are apps that do-everything; mega-platforms unto themselves. They are particularly prevalent in East Asia. Like China's WeChat or South Korea's KakaoTalk, Japan's LINE has evolved from a single purpose chat app to the do-everything platform for everyday cultural and economic activities. It is also the very reason for the global proliferation of stickers or large-size emoji in other chat apps, from Apple's iMessage to Facebook's Messenger to Tencent's WeChat. This article offers a close examination of LINE to highlight and theorize the process of the "platformization of cultural production." To do so, it traces Japan's longer history of platforms going back to the i-mode mobile platform launched in 1999, and examines LINE's regionally specific sticker-oriented strategies in East Asia. With a focus on the entrepreneurial work of sticker designers as cultural producers, this article also mobilizes LINE to both highlight the specificities of this platform and contest the excessive attention paid to platforms from Silicon Valley, or, at best, their Chinese counterparts. LINE and the regional convergences of super apps in East Asia are a potent reminder of the need to analyze platforms outside of the bi-polar hegemony of the United States versus Chinese tech world—which increasingly frames journalistic discourse and academic research—and of the need to attend to the historical and regional particularities of platforms and their cultural impacts.